2015
DOI: 10.1037/apl0000018
|View full text |Cite
|
Sign up to set email alerts
|

A suggestion to improve a day keeps your depletion away: Examining promotive and prohibitive voice behaviors within a regulatory focus and ego depletion framework.

Abstract: One way that employees contribute to organizational effectiveness is by expressing voice. They may offer suggestions for how to improve the organization (promotive voice behavior), or express concerns to prevent harmful events from occurring (prohibitive voice behavior). Although promotive and prohibitive voices are thought to be distinct types of behavior, very little is known about their unique antecedents and consequences. In this study we draw on regulatory focus and ego depletion theories to derive a theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
292
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(308 citation statements)
references
References 80 publications
(211 reference statements)
13
292
1
2
Order By: Relevance
“…In this way, employees exercising prohibitive voice may be concerned that their supervisor will view the prohibitive voice as disruptive to task progress (Burris, 2012). Riskaverse people will use this communication type with caution or never use it (Lin & Johnson, 2015). This risk-avoidance tendency might be more aggravated in the Chinese context of this study which values harmony and relationships (Bai, Han, & Harms, 2016;Bai, Harms, Han, & Cheng, 2015;Bai, Li, & Xi, 2012).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, employees exercising prohibitive voice may be concerned that their supervisor will view the prohibitive voice as disruptive to task progress (Burris, 2012). Riskaverse people will use this communication type with caution or never use it (Lin & Johnson, 2015). This risk-avoidance tendency might be more aggravated in the Chinese context of this study which values harmony and relationships (Bai, Han, & Harms, 2016;Bai, Harms, Han, & Cheng, 2015;Bai, Li, & Xi, 2012).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The motivation behind prohibitive voice is to pull organizations away from feared states (Lin & Johnson, 2015). In spite of its potential and intended benefits, compared to promotive voice behavior, prohibitive voice carries high interpersonal risks (Liang et al, 2012).…”
Section: Ethical Leadership and Employee Voicementioning
confidence: 99%
See 1 more Smart Citation
“…To date, research on regulatory fit has mostly examined consequences in achievement domains, such as its effects on individual effort and task performance (Spiegel, Grant‐Pillow, & Higgins, ; Venus, Stam, & van Knippenberg, ) as well as company performance and acquisitions (Gamache, McNamara, Mannor, & Johnson, ; Wallace, Little, Hill, & Ridge, ). Organizational research in particular has emphasized the achievement‐based consequences of regulatory focus and fit, such as productivity (Wallace & Chen, ), safety performance (Kark, Katz‐Navon, & Delgatch, ), voice behaviour (Lin & Johnson, ) and reactions to task feedback (Van Dijk & Kluger, , ). However, the effects of regulatory focus likely extend to other domains as well.…”
Section: Introductionmentioning
confidence: 99%
“…Prevention focus has positive prediction of the deviant behavior and promotion focus has positive prediction of helping behavior. Lin and Johnson (2015) studied and examined the relationship between promotion focus and verbal advice behavior of employee through the longitudinal, which found that employee's promotion focus can enhance their increase both promotional and prohibitive verbal advice behavior of employee, while prevention focus can only enhance the worker's prohibitive verbal advice behavior.…”
Section: Effects Of Regulatory Focusmentioning
confidence: 99%